Effectiveness of Hesabyar Cognitive Rehabilitation on Neuropsychological Functions of Children with Special Learning Disabilities - Mojtaba Ebrahimi; Fereshteh Baezzat; Vahid Nejati; Soheila Hashemi (Shiraz University of Medical Sciences, 2022)
Background: Children with learning disabilities have cognitive impairments not attributable to their intelligence. The present study aimed to evaluate the effectiveness of Hesabyar Cognitive Rehabilitation on neuropsychological functions of children with special learning disabilities.Methods: This was a quasi-experimental study which had pre-test and post-test design and conducted with a control group. The statistical population included all the male elementary students with special learning disabilities in Semnan, Iran, in the academic year 2019-2020. The sample consisted of 40 students (20 participants in each group) with special learning disabilities that were treated. The Conners Psychological Scale was used for data collection. The experimental group underwent cognitive load rehabilitation every other day for 10 sessions while the control group did not receive any treatment. The data were analyzed using the statistical method of multivariate analysis of covariance and SPSS version 24.Results: The mean±SD of age in the experimental group and the control group were respectively 11.2±0.9 and 11.5±0.8. The results of ANCOVA analysis showed that Hesabyar Cognitive Rehabilitation program made significant changes in components of variables, including selective attention (P=0.002), sustain attention (P=0.001), attention shifting (P=0.001), attention divided (P=0.004), attention span (P=0.002) l-term memory (P=0.011) [components of difficulty in memory function and learning], executive functions (P=0.001), problem with speed and cognitive processing ability (P=0.016), as well as components of academic performance problems, namely attention functions (P=0.004), computational science (P=0.002), argument/calculations (P=0.014), and attitudinal discussions (P=0.001) [components of academic performance problems: mathematics].Conclusion: Based on the findings of this study, Hesabyar Cognitive Rehabilitation program is one of the treatments that can be used to minimize the problems of students with math learning disorders.